O coordenador pedagógico da Educação Infantil na perspectiva de seus professores - Santos, Luízyana Magda Coêlho dos (2017)
This dissertation has Early Childhood Education as its theme and aims to analyze the Nursery Education Pedagogical Coordination professional, from the perspective of their teachers, who are active in a public daycare and preschool in a county in São Paulo Metropolitan Area. The research, from a qualitative approach, has used the interview in the reflective modality as a tool. Six preschool teachers were interviewed. The theoretical referring was composed of Early Childhood Education scholars such as Campos (2006), Kuhlmann (2000), Rosemberg (1994), Oliveira (2011), Rizzo (2003), Kishimoto (1998), and, regarding Pedagogical Coordination Placco, Almeida, Souza (2012) and Zumpano, Almeida (2012). The discussion of produced information has enabled the comprehension not only of the interviewed teachers’ profile but also of their vision regarding Pedagogical Coordination performance in their units. The speeches of the interviewed coordinators also revealed: providing the child development, they promote their own professional development; the teacher’s continuing education must be the Pedagogical Coordinator priority; and, that the daycare and preschool professional need to identify the knowledge and informations which the children already possess when they reach the School